Penerapan Metode Algoritma C4.5 Untuk Memprediksi Loyalitas Karyawan Pada PT.Tolan Tiga Indonesia Perlabian Estate - Rambe, Diana Indriani; Nasution, Marnis; Muti Ah, Rahma (Jurnal Informatika, 2024)
The capital market is a place where various financial instruments are sold and bought can be long-term or short-term financial instruments. The Indonesian stock market is regulated by law No. 8 of 1995 capital market. The law clarifies the role of capital markets in the country's economy. The capital market has two functions, namely as a container for corporate financing in collecting funds from investors and as a means of investment. Loyalty is a person's loyalty in serving in a company or institution where there is a dedication and trust given by the company or institution in carrying out tasks in accordance with its expertise. in which there is a sense of love and responsibility to strive to provide the best service and behavior to show good work performance. . Loyalty is needed by companies because if employees do not have loyalty at work, it can harm the company. Thus in order to determine employee loyalty,several assessments are needed such as : employee performance,neatness in work, behavior and frequency of cooperation. Sehinnga from the assessment the company can assess how employee loyalty and if the contract employees include employees who have loyalty to the work it will be adopted as permanent employees at PT. There Are Three Types Of Indonesian Real Estate. The need for information services is very important, in predicting employee loyalty .in predicting employee loyalty can still be done manually but requires a very long processing time can be days.therefore, the author provides convenience with the use of meaching learning method, namely C4. 5 algorithm . C4.5 algorithm can facilitate the company in the process of employee prediction with just a matter of hours. So that it can make it easier for companies to determine employees who have loyalty to PT. There are three types of Indonesian real Estate.